Sobrevida e causas de descontinuidade do primeiro anti tnf na Espondilite Anquilosante comparado com Artrite Reumatoide : análise do BiobadaBrasil - Fafá, Bárbara Petronetto (2014)
Introduction: Treatment survival with biological therapy may be influenced by many factors and it seems to be different among various rheumatic diseases and biological agents. Objective: To compare the survival and causes of the discontinuation of antitumoral necrosis factor (anti TNF) therapy in Ankylosing Spondylitis (AS) with Rheumatoid Arthritis (RA). Methods: A population-based cohort of AS and RA patients from the Brazilian Registry of Biological Therapies in Rheumatic Diseases (BiobadaBrasil) included between 2008-2013. The observation time was up to 4 years following the introduction of the first treatment. Sex, age, disease duration, disease activity, comorbidities and concomitant therapies were assessed. Kaplan-Meier curve, Chisquare, Kruskal-Wallis and Wilcoxon-Mann-Whitney tests and Cox regression were used whenever appropriated. The p value < 0.05 was considered significant. Results: 1.303 patients were included, 67.2% were women, 50.5 ± 12.6 years old, 372 (28.5%) had AS and 931 (71.5%) had RA. As to the biological class of their anti TNF therapy, 38.7% (n = 504) used infliximabe (IFX), 34.9% (n = 455) used adalimumabe (ADA) and 26.4% (n = 344) used etanercepte (ETA). Patients with AS had highter retention rate (82.3 % vs 67.3%; p ≤ 0.001) and higher survival (42.67 ± 0.67, CI = 41.34-43.99 vs. 36.83 ± 0.54, CI = 35.77-37.89 months; p ≤ 0.001). Patients with SA have half risk of anti TNF discontinuation (odds = 0.455, p<0.001), regardless of sex and age. Discontinuation due to ineffectiveness (6.2% vs 15.8%, p<0.001) and adverse event (5.9% vs. 11.3%, p.003) was smaller in AS. Survival was similar to all 3 anti TNF for SA. The RA showed best retention rate for ETA compared to ADA and IFX in the RA. The risk of ETA discontinuation was lower than the IFX (HR = 0.72 (IC= 0.53-0.96). Age, sex, medication, disease activity, disease duration, HLA B27 and rheumatoid factor were not associated with treatment discontinuity in both disease. Conclusion: AS patients have higher survival by treatment with anti TNF independent of sex and age. They also have a lower rate of serious adverse events and seem to be related to the disease mechanism, since they have a lower rate of inefficiency.